MENINGKATKAN KETERAMPILAN SAINS ANAK MELALUI KEGIATAN EKSPLORASI BAHAN ALAM (Penelitian Tindakan pada Sentra Bahan Alam Kelompok B di TK Az-zahroh Serang-Banten) - Kusniati Kusniati; Ratih Kusumawardani; Kristiana Maryani (Jurnal Penelitian dan Pengembangan Pendidikan Anak Usia Dini, 2017)
This study aims to 1) to know the process of applying natural resource exploration activities in improving science skills of group B children in TK Az-zahroh Serang-Banten, and 2) to improve children’s science skills through natural resource exploration activities in group B in TK Az-zahroh Serang-Banten. The research type is action research using model of kemmis and MCTaggart. The research subject is 15 children aged 5-6 years in kindergarten Az-zahroh Serang-Banten. The object of research is children’s science skills. Data collection method is done through observation, interview and documentation. Data analysis technique is done qualitatively and quantitatively. The success indicator in this research is 60%. The results showed that children’s science skills increased to 80% from pre-research results of 39% up in cycle I of 51% of the results can be concluded that the exploration activities of natural materials can improve the science skills of children aged 5-6 years in kindergarten Az-zahroh Serang-Banten.